2023
DOI: 10.3390/phycology3010012
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Spirogyra sp. and Chlorella sp. in Bioremediation of Mine Drainage: A Review

Abstract: One of the biggest global challenges in the mining industry is managing the risks associated with contamination by potentially toxic elements (PTEs) resulting from their activity. The oxidation of sulfides is the main cause of polluted mine drainage through the leaching of PTEs from mine waste and mine galleries to the water systems. Mine drainage can be highly acidic and often has a high concentration of PTEs, particularly arsenic, one of the environment’s most toxic elements. PTEs endanger the ecosystem’s eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…They have also emerged as a potential substrate in bioremediation processes of wastewater and polluted ecosystems through their capacity to adsorb and accumulate toxic compounds. 12–14 In order to enhance their contaminant removal efficiency, various strategies have been proposed, such as cells immobilization or development of algal consortia in biofilm-based cultures ( cf. e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also emerged as a potential substrate in bioremediation processes of wastewater and polluted ecosystems through their capacity to adsorb and accumulate toxic compounds. 12–14 In order to enhance their contaminant removal efficiency, various strategies have been proposed, such as cells immobilization or development of algal consortia in biofilm-based cultures ( cf. e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an illustration, strong variations of pH, as met in acid mine drainage, can dramatically affect the bioremediation capacity of microalgae due to unfavourable change in their electrostatic interactions with heavy metals. 12 Besides, proper modification of pH condition in cell culture media is one of the possible microalgae harvesting method employed to generate auto-flocculation 21–23 or enhance the effects of flocculants. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that microalgae and cyanobacteria carry out oxygenated photosynthesis even with small amounts of photosynthetic oxygen, help in electrogenesis, wastewater treatment (via anodic oxidation and cathodic reduction), and CO 2 capture (via cathodic reduction) [21,22]. Also, it has been shown that even small amounts of photosynthetic oxygen in the anode of microbial fuel cells have been able to benefit the growth of heterotrophic bacteria, which has managed to generate an certain level of electrical current [23,24].…”
Section: Introductionmentioning
confidence: 99%